2010
DOI: 10.1111/j.1365-2966.2010.16351.x
|View full text |Cite
|
Sign up to set email alerts
|

Population III star clusters in the reionized Universe

Abstract: In reionized regions of the Universe, gas can only collapse to form stars in dark matter (DM) haloes which grow to be sufficiently massive. If star formation is prevented in the minihalo progenitors of such DM haloes at redshifts z≳ 20, then these haloes will not be self‐enriched with metals and so may host Population (Pop) III star formation. We estimate an upper limit for the abundance of Pop III star clusters which thus form in the reionized Universe, as a function of redshift. Depending on the minimum DM h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 128 publications
(204 reference statements)
0
10
0
Order By: Relevance
“…about around the end of the cosmic dark ages) (for models indicating late, z ∼ 2 − 7, Pop III star formation, see Refs. [1281,1282]).…”
Section: Iii7 Age Of the Universementioning
confidence: 99%
“…about around the end of the cosmic dark ages) (for models indicating late, z ∼ 2 − 7, Pop III star formation, see Refs. [1281,1282]).…”
Section: Iii7 Age Of the Universementioning
confidence: 99%
“…This leads to a scenario in which the first galaxies that appeared in the Universe (in the chronological sense) were mostly Pop II galaxies; Pop III galaxies would appear subsequently in underdense regions where the star formation in minihalos was suppressed by radiation emitted by stars/galaxies formed earlier in overdense regions. For this reason, Pop III galaxies may be considered as the second-generation galaxies containing first-generation stars (e.g., Johnson, Greif, & Bromm 2008;Trenti & Stiavelli 2009;Johnson 2010;Stiavelli & Trenti 2010;Johnson, Dalla Vecchia, & Khochfar 2013).…”
Section: First Objects: Current Picturementioning
confidence: 99%
“…Although detecting genuine Pop III objects at high redshift will likely require strong boosting of H 2 line luminosities by some mechanism as well as lensing amplification, SAFARI may be able to probe the properties of such objects through the observations of similarly metal-poor objects that may exist at lower redshift. For example, a number of studies have suggested that Pop III star formation may continue towards low redshift and maybe even down to z ∼ 3 (e.g., Scannapieco, Schneider, & Ferrara 2003;Jimenez & Haiman 2006;Schneider et al 2006a;Tornatore, Ferrara, & Schneider 2007;Ricotti, Gnedin, & Shull 2008;Trenti & Stiavelli 2009;Johnson 2010;Johnson et al 2013;Pallottini et al 2014Pallottini et al , 2015a. According to the recent Renaissance Simulations (Xu et al 2016), only 6% of the volume and 13% of the gas mass are enriched to [Z/H] > −4 at z = 7.6 in the comoving survey volume of 220 Mpc 3 , indicating that there is a large amount of pristine gas available for Pop III star formation at z < 7.6 (although much of it likely resides in low-density diffuse IGM).…”
Section: Pop III Objects At Lower Redshiftmentioning
confidence: 99%
“…This is because the lifetimes of massive (M 100 M⊙) Pop III stars are only a few Myr (Schaerer 2002), leading to prompt enrichment of metals via supernovae winds and a transition to Population II (Pop II) stars. However, it has been proposed that Pop III stars could form in much more massive halos if star formation is suppressed in all progenitor halos via strong ionizing radiation (Johnson 2010;Visbal et al 2016;Yajima & Khochfar 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For the three halos tested, we find that an ionizing photon flux of at least ≈ 10 6 s −1 cm −2 is required to suppress star formation significantly above the atomic cooling threshold. At high-redshift, this is most likely to occur in close proximity to large star-forming galaxies (Johnson 2010;Visbal et al 2016).…”
Section: Introductionmentioning
confidence: 99%